Shikhara of the Mukhamandapa - Temples of India Project Team (Jio Institute, 2024)
The frontal pediment of the shikhara (superstructure) of the mukhamandapa (front porch) depicts locked doors, which is the most distinct element of the pediment, used here as a decorative motif. These closed doors represent the types of wooden doors that were used in the region during this period. The depiction is noteworthy as it also depicts a variety of heavy locks which were used in the old havelis of Rajasthan. Such representation of doors and locking systems is rarely found in temples, making the presence of these elements as decorative motifs in this temple particularly unique.